Mga pambansang bangungot a critical readingf of narratives in Chito's S. Rono's selecte3d horror films as allegories of Filipino Society. - Abalajon, Eric P. (2014.)
It took some time before cinema become a legitimate art form worthy as an object of study. Francois Truffaut proposed the concept of the auteur where though a large number of people are involved in producing a film, the director has overall artistic power in the movie. This formal approach to the medium invariably leads to the neglect of ?genre films?. Cultural studies made possible the evaluation of these popular movies by placing them in their social and historical contexts. Using an interdisciplinary approach that gives equal value to both text and context, the dynamics of society and cultural artifacts are revealed in films. The paper will focus on the relatively neglected genre of horror cinema, particularly the work of veteran director Chito S. Roño. The paper aims to document the film career of Chito S. Roño and locate his position in the development of Filipino film industry. The paper then pursues a reading of a range of recent blockbuster horror films?Feng Shui (2004), T2 (2009), and The Healing (2012)?and highlight their sociocultural and political underpinnings. Lastly this study aims to discuss the dynamics of horror films, particularly its allegorical function, and the role it plays in Philippine society. Feng Shui (2004) is read as a demonstration of overlapping societal anxieties regarding the discourse of upward economic mobility that spills over to the discourses of luck, ethnicity, changing gender roles and politics of domestic space. T2 (2009) is read as a reworking of the road movie, juxtaposing the discourse of spatial politics and majority-minority antagonisms in the nation-space. The source of horror is read as the unresolved issues brought about by the subalternization of Filipino-Muslims. The Healing (2012) is read in the context of dismal state of health care and disintegration of the sense of community; the critique maps the horrors that confront the Filipino body and lays bare possible resistance. This paper takes the position that indeed the selected horror films once historicized perform allegorical functions, and by infusing forms of resistance in the narratives can also help to usher in social transformation to end societal horrors.
Research Paper (Undergraduated, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2014.
Keywords: Chito Rono -- Research; Films -- Horror -- Research